Recent Advances in Copper-Catalyzed Asymmetric Hydroboration of Electron-Deficient Alkenes: Methodologies and Mechanism - Chen, Jing-Biao; Whiting, Andrew (Synthesis, 2018)
The efficient synthesis of enantioenriched organoboron compounds has been recognized as an important topic in recent years. As an update review, this article aims to select key achievements in copper-catalyzed, electron-deficient alkene enantioselective hydroboration methodologies since the beginning of 2017. In addition, it covers relevant mechanistic investigations developed over the last six years, as well as total synthesis applications for preparing 1,3-diols as important medicinal intermediates.1 Introduction2 Methodologies for Copper-Catalyzed Hydroboration2.1 α,β-Unsaturated Ketones and Imines2.2 α,β-Unsaturated Esters and Cyanides2.3 Aryl Alkenes and Alkyl Alkenes3 Mechanistic Investigations on the Copper-Catalyzed Hydroboration3.1 A Cu–BX2 Intermediate3.1.1 Experimental Analysis3.1.2 Borylative Difunctionalization Methodologies3.1.3 Density Functional Theory3.2 A Cu–H Intermediate3.3 Other Mechanistic Proposals4 Synthetic Applications: Chiral 1,3-Diols5 Conclusions and Outlook
Keywords: alkenes; copper catalysis; hydroboration; asymmetric; mechanism; 1,3-diols; total synthesis